A Review on Utilization of Waste Materials in Construction of Rigid Pavement - Arvind Kumar; Anupam Kumar Gautam (International Journal of Scientific Research in Civil Engineering, 2024)
The goal of the project is to find the best waste materials generated by various industries and the environment as a substitute for cement and aggregate in highway construction. Several studies have been undertaken across the world to determine the negative impact of various waste items on the environment and human health. Therefore it becomes important to find the best replacement of cement with other materials having similar binding properties and required strength. The use of waste materials in the rigid construction reduces the use of cement which is causing a lot of harmful effects and there is a significant reduction in the cost of the materials. The man behind the use of waste materials in the rigid pavement must have precise knowledge about the design and its characteristics. As a result, mistakes in design or construction, as well as poor material selection, have a significant impact on the pavement’s service life. It is also demonstrated that the durability of concrete pavements is not just dependent on the quality of the concrete, but also on effective site-building methods such as placing, compaction, and curing. Pavement engineers must therefore comprehend and solve concerns such as suitable material selection, mixed design and details, prevailing drainage conditions, construction processes, and pavement performance. This project mainly focuses on the use of plastic waste and Electric Arc Furnace (EAFS) as a replacement for coarse aggregate and cement respectively. Different tests were performed on cement, Plastic waste, and EAFS to check the standards values of the materials and their ranges. A relationship was established between different proportions of plastic aggregate and EAFS vs. compressive strength value to see the optimum value of the plastic aggregate and EAFS as the replacement of natural coarse aggregate and cement respectively. Finally, the theoretical strengths collected from different research papers of different proportions are being compared to the laboratory values for 7, 14, and 28 days, to check their compressive, tensile, and flexural strengths. By 20% replacement of cement by EAFS there is an increment of 4.58MPa for the compressive strength of 7 days. For the 28 days, the highest value was recorded for unmodified concrete.